2012
DOI: 10.1080/10401334.2012.692267
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges in Integrating Electronic Health Records Into Undergraduate Medical Education: A National Survey of Clerkship Directors

Abstract: Medical students are using electronic health records at higher rates than physicians in practice. Although this is overall reassuring, educators have to be cautious about the limitations being placed on student's documentation in electronic health records as this can potentially have consequences on their training, and they need to explore ways to maximize the benefits of electronic health records in medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
92
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 15 publications
2
92
0
Order By: Relevance
“…12 According to a recent survey of clerkship directors by the Alliance of Clinical Education (ACE), only an estimated 64% of programs currently allow students any use of EHRs; of these only two thirds allowed students to write notes within the electronic record. 13 Overall, clerkship directors acknowledged many advantages to EHRs, but many educational concerns were raised regarding their current use.…”
Section: Introductionmentioning
confidence: 99%
“…12 According to a recent survey of clerkship directors by the Alliance of Clinical Education (ACE), only an estimated 64% of programs currently allow students any use of EHRs; of these only two thirds allowed students to write notes within the electronic record. 13 Overall, clerkship directors acknowledged many advantages to EHRs, but many educational concerns were raised regarding their current use.…”
Section: Introductionmentioning
confidence: 99%
“…Students identified a number of benefits of using the educational EHRs over the traditional procedure of recording patient data. The results of this study stressed the importance of integrating EHR training from Hammoud et al [16]conducted a study to describe the earlier clinical encounters and integrating EHR-related learning objectives into the program curriculum. The study noted that further research is required to empirically evaluate the impact of educational EHR systems.…”
Section: B Using Ehrs In Educational Settingsmentioning
confidence: 99%
“…that the student could consider in this patient. found that only two-thirds of institutions allowed students to 536 write notes in the EMR [46]. However, institutions embracing the 537 EMR for educational purposes may find great value to both the trai-538 nee and medical team in trainee-authored content in the EMR 539 [47,48].…”
mentioning
confidence: 99%